Orientation-Mediated Luminescence Enhancement and Spin-Orbit Coupling in ZnO Single Crystals - Hassan, Ali; Khan, Abbas Ahmad; Ahn, Yeong Hwan; Azam, Muhammad; Zubair, Muhammad; Xue, Wei; Cao, Yu (Nanomaterials, 2022)
Temperature-, excitation wavelength-, and excitation power-dependent photoluminescence (PL) spectroscopy have been utilized to investigate the orientation-modulated near band edge emission (NBE) and deep level emission (DLE) of ZnO single crystals (SCs). The near-band-edge emission of ZnO SC with <0001> orientation exhibits strong and sharp emission intensity with suppressed deep level defects (mostly caused by oxygen vacancies Vo). Furthermore, Raman analysis reveals that<0001> orientation has dominant E2 (high) and E2 (low) modes, indicating that this direction has better crystallinity. At low temperature, the neutral donor-to-bound exciton (Do X) transition dominates, regardless of the orientation, according to the temperature-dependent PL spectra. Moreover, free-exciton (FX) transition emerges at higher temperatures in all orientations. The PL intensity dependence on the excitation power has been described in terms of power-law (I~Lα). Our results demonstrate that the α for <0001>, <1120>, and <1010> is (1.148), (1.180), and (1.184) respectively. In short, the comprehensive PL analysis suggests that Do X transitions are dominant in the NBE region, whereas oxygen vacancies (Vo) are the dominant deep levels in ZnO. In addition, the <0001> orientation contains fewer Vo-related defects with intense excitonic emission in the near band edge region than other counterparts, even at high temperature (~543 K). These results indicate that <0001> growth direction is favorable for fabricating ZnO-based highly efficient optoelectronic devices.
Keywords: exciton; impurities and defects; photoluminescence; single crystal; zinc oxide